Amino Acids Catalyzed Biginelli Protocols - Madeeha Zafar, Ansa; Qureshi, Saira; Naeem Khan, Muhammad; Azad, Muhammad; Ali Munawar, Munawar; Ain Khan, Misbahul (Asian Journal of Chemistry, 2013)
Various amino acids were found to be excellent catalysts for the Biginelli dihydropyimidone synthesis. The method is simple and provides an alternate and efficient catalyst for the multiple component reactions.